Finanzas y contabilidad en minería: Evaluación económica de la empresa Cementos Pacasmayo - Lizarzaburu B., Edmundo (2019)
The economic valuation consists on the economic studies of the country, sector and company, which allow the appraiser to exercise certain parameters or assumptions for the elaboration of a model that approximates the value of the company in the present value. In this research the methodology of valuation is explained in a practical way using as a proof the company Cementos Pacasmayo, where a cash flow model discounted to 10 years was presented and brought to present value using a discount rate (WACC) composed by the cost of debt and the cost of capital of the company mentioned.